Development of RAG2-/-IL2Rγ-/Y immune deficient FAH-knockout miniature pig - Zhao, Heng; Ye, Weijian; Guo, Jianxiong; Wang, Jiaoxiang; Jiao, Deling; Xu, Kaixiang; Yang, Chang; Chen, Shuhan; Jamal, Muhammad Ameen; Bai, Zhongbin; Wei, Taiyun; Cai, Jie; et al. (Frontiers in Immunology, 2022)
Human hepatocyte transplantation for liver disease treatment have been hampered by the lack of quality human hepatocytes. Pigs with their large body size, longevity and physiological similarities with human are appropriate animal models for the in vivo expansion of human hepatocytes. Here we report on the generation of RAG2-/-IL2Rγ-/-FAH-/- (RGFKO) pigs via somatic cell nuclear transfer and CRISPR/Cas9. We showed that thymic and splenic development in RGFKO pigs was impaired. V(D)J recombination processes were also inactivated. Consequently, RGFKO pigs had significantly reduced numbers of porcine T, B and NK cells. Moreover, due to the loss of FAH, porcine hepatocytes continuously undergo apoptosis and consequently suffer hepatic damage. Thus, RGFKO pigs are both immune deficient and constantly suffer liver injury in the absence of NTBC supplementation. These results suggest that RGFKO pigs have the potential to be engrafted with human hepatocytes without immune rejection, thereby allowing for large scale expansion of human hepatocytes.